Brief isoflurane administration as an adjunct treatment to control organophosphate-induced convulsions and neuropathology - Puthillathu, Narayanan; Moffett, John R.; Korotcov, Alexandru; Bosomtwi, Asamoah; Vengilote, Ranjini; Krishnan, Jishnu K. S.; Johnson, Erik A.; Arun, Peethambaran; Namboodiri, Aryan M. (Frontiers in Pharmacology, 2023)
Organophosphate-based chemical agents (OP), including nerve agents and certain pesticides such as paraoxon, are potent acetylcholinesterase inhibitors that cause severe convulsions and seizures, leading to permanent central nervous system (CNS) damage if not treated promptly. The current treatment regimen for OP poisoning is intramuscular injection of atropine sulfate with an oxime such as pralidoxime (2-PAM) to mitigate cholinergic over-activation of the somatic musculature and autonomic nervous system. This treatment does not provide protection against CNS cholinergic overactivation and therefore convulsions require additional medication.Benzodiazepines are the currently accepted treatment for OP-induced convulsions, but the convulsions become refractory to these GABAA agonists and repeated dosing has diminishing effectiveness. As such, adjunct anticonvulsant treatments are needed to provide improved protection against recurrent and prolonged convulsions and the associated excitotoxic CNS damage that results from them. Previously we have shown that brief, 4-minute administration of 3% to 5% isoflurane in 100% oxygen has profound anticonvulsant and CNS protective effects when administered 30 minutes after a lethal dose of paraoxon. In this report we provide an extended time course of the effectiveness of 5% isoflurane delivered for 5 minutes, ranging from 60 to 180 minutes after a lethal dose of paraoxon in rats. We observed substantial effectiveness in preventing neuronal loss as shown by Fluoro-Jade B staining when isoflurane was administered 1 hour after paraoxon, with diminishing effectiveness at 90, 120 and 180 minutes. In vivo magnetic resonance imaging (MRI) derived T2 and mean diffusivity (MD) values showed that 5-minute isoflurane administration at This is a provisional file, not the final typeset article a concentration of 5% prevents brain edema and tissue damage when administered 1 hour after a lethal dose of paraoxon. We also observed reduced astrogliosis as shown by GFAP immunohistochemistry. Studies with continuous EEG monitoring are ongoing to demonstrate effectiveness in animal models of soman poisoning.